EXPERIENCE OF USING MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE PROFESSIONAL TRAINING OF FUTURE DENTISTS - Gevkaliuk, Nataliia; Martyts, Yurii; Mykhailiuk, Vitalii; Pynda, Mariana (Eastern Ukrainian Medical Journal, 2025)
The objective of the research is to justify the appropriateness, possibilities and peculiarities of using information and communication technologies in the educational activities of the Ivan Horbachevsky Ternopil National Medical University, considering the advancing global innovations in medical science and practice. Materials and methods. The following scientific methods were applied: a) theoretical – analysis of psychological and pedagogical scientific literature to summarize domestic and international experience in the application of modern digital technologies in higher education institutions; b) empirical – pedagogical observations of the educational activities of the environment’s subjects using information and communication technologies, surveys, interviews, anonymous questionnaires of dental students to assess the effectiveness of the functioning of modern digital technologies; c) statistical – descriptive statistics for the analysis and interpretation of research results. Results. The article describes the experience and peculiarities of using digital technologies in the educational activities of Ivan Horbachevsky Ternopil National Medical University. The study of the advanced experience in European and American medical education in higher education institutions contributed to the adoption by the academic council of Ivan Horbachevsky Ternopil National Medical University of the Development Concept "Integration into the World Medical Education Space", which marked the beginning of the implementation of modern educational technologies. The article provides an overview of the university’s information technology platform in the training of medical professionals, describes the current state of distance education, its features in forming the general and professional competencies of future doctors using interactive methods, rational organization of students’ independent work using innovative forms and digital technologies. An analysis of anonymous student surveys on the effectiveness of the existing educational process organization at Ivan Horbachevsky Ternopil National Medical University using the resources of modern information and communication technologies has been conducted. Conclusion. Modern digital technologies prove to be an effective educational tool in the professional training of future medical professionals. An analysis of the conducted anonymous survey has shown that the majority of students confirmed the appropriateness and effectiveness of using computer-oriented educational environment resources as a means of organizing pedagogical interaction at Ivan Horbachevsky Ternopil National Medical University.